Birthweight and urinary incontinence after childbirth: a systematic review and meta-analysis - Stian Langeland Wesnes; Elin Seim (Elsevier, 2020)
Birthweight and urinary incontinence after childbirth: a systematic review and meta-analysisStian Langeland WESNES, Elin SEIM MDUrinary incontinence (UI) is common after childbirth. Many cohort and cross-sectional studies have reported data on birthweight, but results have not been pooled. It is unclear how birthweight affects UI after childbirth. The objective is to review the effect of birthweight on UI after childbirth through meta-analyses.Searches were performed in Medline, Embase, Svemed+, ClinicalTrials.gov, Cochrane, and Cinahl in August 2016. Additional reference checking was performed. Included articles evaluated birthweight as a possible risk factor for maternal UI. We included articles that were presented in Norwegian, Danish, Swedish, or English. Two independent reviewers extracted the data and analysed it using Review Manager 5.3 software. Available data from included studies on birthweight (≥4000 g and ≥3500 g, respectively) and UI were combined in meta-analyses. PRISMA and MOOSE guidelines were used.Eighteen studies (N = 30 070) reported data on birthweight >4000 g vs <4000 g. Birthweight>4000 g compared to weight <4000 g was associated with a significantly increased OR of any UI (OR 1.49, 95% CI 1.24 - 1.80). Five studies (N = 15 066) reported data on birthweight >3500 g vs <3500 g. Birthweight>3500 g was also associated with a significantly increased OR of UI (OR 1.26, 95% CI 1.15 - 1.37).High birthweight appears to increase OR of UI after childbirth. Preventative strategies should be targeted towards women at particular risk.